Assessment of irrigation water quality in Isparta Plain (SW- Turkey) using statistic and Geographic Information Systems - Demer, Selma; Hepdeniz, Kerem (Türk Coğrafya Kurumu, 2018)
In this study, the suitability of groundwater for agricultural irrigation in Isparta Plain was evaluated. For this purpose, samples were taken from 21 groundwater wells used for irrigation in agricultural areas in Isparta Plain. The EC, TDS values and chemical index calculations such as SAR, Na %, SSP, RSC, MR, KI, PI and PS were performed for the evaluation of irrigation water quality. According to the irrigation water criteria, the part of the water samples are in the “permissible” class for EC values and the high salinity/low sodium class, C3-S1 group, in the US Salinity diagram classification. The other part of the water samples are classified as the medium salinity C2-S1 group which can be used for all plants without the danger of salinity and sodium and as the “good” irrigation waters. All water samples have hardness values ranging from moderate water to very hard water according to TH values. The waters in the study region are determined as “good” to “excellent” in terms of Na % and SSP values, “excellent” in terms of SAR values, and “good” quality in terms of PI values for irrigation characteristics. All of the waters in the study area are suitable for irrigation purposes when considering the RSC, MR, KI, PS values. However, these chemical index parameters have been classified using scaled symbols according to the data sizes in the Geographic Information Systems program on the basis of irrigation water quality criteria. In these evaluations, it was determined that chemical index parameters have differed in some locations, but all of the waters are groundwater with suitable qualities for agricultural usage.

Bu çalışmada, Isparta Ovası’nda yeraltısularının tarımsal sulama için uygunluğu değerlendirilmiştir. Bu amaçla Isparta Ovası’nda sulama amacıyla kullanılan 21 adet yeraltısuyu kuyusundan örnek alınmıştır. Sulama suyu kalitesinin değerlendirilmesinde EC, TDS değerleri ve SAR, % Na, SSP, RSC, MR, KI, PI, PS, TH gibi kimyasal indeks hesaplamaları yapılmıştır. Sulama suyu kriterlerine göre suların bir kısmı EC değerleri bakımından “izin verilebilir” sınıfta, ABD Tuzluluk diyagramı sınıflandırmasında yüksek tuzluluk/düşük sodyum sınıfı olan C3-S1 grubundadır. Diğer bir kısmı ise tuzluluk ve sodyum tehlikesi oluşturmadan tüm bitkiler için kullanılabilen, orta tuzlu C2-S1 grubu ve “iyi” sulama suları olarak sınıflandırılmaktadır. Tüm su örnekleri, TH değerlerine göre orta sertlikte sulardan çok sert sulara kadar değişen sertlik değerlerine sahiptir. Çalışma bölgesindeki sular, % Na ve SSP değerleri açısından “iyi” ile “mükemmel”, SAR değeri açısından “mükemmel”, PI değerleri açısından “iyi” kalitede özelliğe sahip sulama suları olarak belirlenmiştir. RSC, MR, KI, PS değerleri göz önünde bulundurulduğunda ise çalışma alanındaki suların tümünün sulama amacıyla kullanımı uygundur. Bununla birlikte, bu kimyasal indeks parametreleri sulama suyu kalite kriterleri temelinde Coğrafi Bilgi Sistemleri programında veri büyüklüklerine göre derecelendirilmiş semboller kullanılarak sınıflandırılmıştır. Bu değerlendirmelerde, bazı lokasyonlarda kimyasal indeks parametrelerinin farklılık gösterdiği ancak suların tümünün tarımsal amaçla kullanıma uygun niteliğe sahip yeraltısuları olduğu belirlenmiştir.
Isparta Ovasında (GB-Türkiye) sulama suyu kalitesinin istatistik ve Coğrafi Bilgi Sistemleri kullanılarak değerlendirilmesi